Svobodu plennikam fashizma! - Karachenkov, P (ОГИЗ - ИЗОГИЗ (Izogiz), 1935)
Imprisoned man with red cloth reaching for bars of cell as uniformed arms attempt to drag him back Original title: Свободу пленникам фашизма!. Suggested translation: Freedom to prisoners of fascism! PO-0011